ANSWER
x = 20
Step-by-step explanation
To solve this equation, first, we have to subtract 11 from both sides,
![\begin{gathered} \log_6(2x-4)+11-11=13-11 \\ \\ \log_6(2x-4)=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/be7frnijm2ibhxqa0bhjr04t7x9p82gssn.png)
Then, there is the property of logarithms that states that if we raise the base of a logarithmic expression to the expression, the result is the argument of the logarithm,
![a^(\log_a(b))=b](https://img.qammunity.org/2023/formulas/mathematics/college/mbijwbw05hdm7kqzah63qp5yx6y3d9o9n7.png)
So, the next step is to raise 6 to each side of the equation,
![\begin{gathered} 6^(\log_6(2x-4))=6^2 \\ 2x-4=36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h2em115w5sa130td2x4sidbr9q0r4m0xv6.png)
Then, add 4 to both sides,
![\begin{gathered} 2x-4+4=36+4 \\ 2x=40 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yc0gqok99elacsnsezjtoxkk8vz9m0fckz.png)
And divide both sides by 2,
![\begin{gathered} (2x)/(2)=(40)/(2) \\ \\ x=20 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/62v3hrmha6d2q9roj81bj8s1z81jdpyein.png)
Hence, the solution is x = 20.